Spatial variation of corn response to nitrogen topdressing in a Cerrado crop field - Hurtado, Sandro Manuel Carmelino; Resende, Álvaro Vilela de; Silva, Carlos Alberto; Corazza, Edemar Joaquim; Shiratsuchi, Luciano Shozo (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the spatial variation of corn response to nitrogen (N) topdressing fertilization, associating the grain yield with indicative variables of the N nutritional status. Four N rates were tested in 12 experimental plots of 12.6x1,200 m. Along each plot, 11 georeferenced sites were located for punctual evaluations. In those sites, the corn nutritional status was monitored using a chlorophyll meter and samples were collected to determine soil mineral N, and N concentration in leaves and grains. The grain yield was mapped using a yield sensor and a Global Positioning System (GPS) device coupled to the combine. The data obtained were analyzed using classical and spatial statistics. The corn with no N topdressing reached an average of 77% of the maximum grain yield (9.21 Mg ha-1) obtained with the usage of topdressing. The high correlation coefficients among the average data of chlorophyll meter readings, leaf N content, and grain yield were not confirmed when the spatial variability of these variables were considered. The map interpretation of the chlorophyll meter readings and corn yield allowed the identification of areas with different soil N supply capacity, indicating field zones for site-specific management.